Multidetector computed tomography identification of previous ablation lines: insights for left atrial flutter ablation. (19th May 2022) - Falasconi, G; Penela, D; Jauregui, B; Soto-Iglesias, D; Teres, C; Ordonez, A; San Antonio, R; Viveros, D; Bellido, A; Scherer, C; Marti, J; Sabate, X; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Left atrial flutter (LAFL) frequently occurs in patients with history of previous left atrial (LA) ablation. LAFL ablation is still considered a challenging and time-consuming procedure (1). Conduction gaps on ablation lines are frequently due to non-transmural or non-contiguous lesions. It was recently demonstrated that aiding AF ablation procedures with the integration of multidetector computed tomography (MDCT)-derived left atrial wall thickness (LAWT) maps into the navigation system allowed decreasing radiofrequency (RF) delivery, fluoroscopy, and procedure time while obtaining a high rate of first-pass isolation (2). Purpose: We hypothesized that MDCT-derived 3D-LAWT map could be useful to aid LAFL ablation procedure in patients with previous LA ablation lines. Methods: Consecutive patients with history of previous LA ablation who underwent LAFL ablation were prospectively enrolled from a single referral center. LAWT three-dimensional maps were obtained from MDCT and integrated into the navigation system. LAWT information was used to focus mapping in the areas of the probable crucial isthmus: the presence of previous ablation lines was searched at the level of linear segments with reduced parietal thickness at the LAWT-maps (LAWT <1mm), while the search for conduction gaps was started at the level of the thicker areas of these lines. Conduction gap was defined as the presence of peak-to-peak bipolar potentials > 0.5 mV at the level of the previous ablation line or as the presence during arrhythmia of a LAT delay <30 ms between contiguous points lying in the same axial plane at the two sides of the line. Ablation was performed transecting the crucial isthmus with the documentation of bidirectional block; ablation first-attempt was guided by color-coded maps by connecting the parts of identified previous ablation lines with reduced LAWT. Finally, RF delivery was adapted to the local LAWT. Results: Five patients [4 (80%) male, age 62 years (57-73)] were included. LAWT-aided LAFL ablation procedures had a median procedure time of 78 minutes (75-114) and a RF time of 5.9 minutes (4.7-8.5); fluoroscopy time was 3.2 minutes (1.5-3.6) with a fluoroscopy dose of 6.1 Gy*cm2 (2.8-8.2). Mean wall thickness of the gap zone was significantly higher with respect to the thickness of the zones of previous ablation lines (1.8 ± 0.5 mm vs. 1.0 ± 0.4 mm, p=0.047). All patients presented sinus rhythm at the end of the procedure and no acute complication occurred. No patient reported arrhythmic recurrence at 1-year follow-up (Figure 2). Conclusions: LAWT-aided approach for LAFL ablation can facilitate identifying the wall thinning produced by the previous RF ablation line and the gap (seen as relative wall thickening) acting as the isthmus for the reentry circuit. This, in turn might help analysis of reentry circuits and increase procedure efficacy and efficiency. Further data are needed to reproduce these findings in a larger study cohort.